Children's Health Insurance Status and Emergency Room Utilization: An Examination of Complex Survey Data. (July 2020) - Muraleetharan, Daenuka; Gilreath, Tamika D.; Primm, Kristin M.; Lautner, Shelby C.
Since the Children's Health Insurance Program's passage into law in 1997, the program has increased in cost to over $15 billion in recent years. Emergency room usage has also increased throughout the United States, leading to nationwide issues in overcrowding and surges in service costs. This study seeks to examine emergency room utilization of children insured under Children's Health Insurance Program to determine if Children's Health Insurance Program enrollees use the emergency room more or less frequently than their privately insured counterparts. The data used in this study were from the 2017 National Health Interview Survey. SAS statistical software was used to conduct a multinomial regression assessing the relationship between insurance type (private v. Children's Health Insurance Program) and frequency of emergency room utilization over the last 12 months. The analysis results indicate no statistically significant difference between Children's Health Insurance Program insured and privately insured children in terms of frequency of emergency room utilization and suggest a need to explore other factors that more directly influence Children's Health Insurance Program costs.